Preliminary analysis of performance differences between elite men and women weightlifters - Cunanan, A. J.; Hornsby, G.; South, M.; Perkins, A.; Pierce, K. C.; Sato, K.; Stone, M. H. (2016)
Weightlifting coaches can evaluate kinematic and kinetic variables to enhance their feedback and instruction and to optimize a periodized training plan. These coaches should be particularly interested in peak barbell velocity during the weightlifting movements (snatch, clean, and jerk), as it is an important determinant of weightlifting performance (Bartonietz, 1996).